INCOME ANALYSIS OF VEGETABLE TRADERS IN AIKMEL TRADITIONAL MARKET AIKMEL SUB DISTRICT EAST LOMBOK REGENCY: INCOME ANALYSIS OF VEGETABLE TRADERS IN AIKMEL TRADITIONAL MARKET AIKMEL SUB DISTRICT EAST LOMBOK REGENCY - muhammad amin (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
Market is a place for public facilities to complete the needs of the community and is a center for community commerce. Not only that, the market continues to play a role for price stability, where market value is one of the benchmarks for assessing inflation. The purpose of this study was to determine the income of vegetable traders in Aikmel Traditional Market, Aikmel District, East Lombok Regency and to find out the obstacles faced by vegetable traders in running their business at Aikmel Traditional Market, Aikmel District. The determination of the research area was carried out by purposive sampling, namely based on certain considerations in accordance with the research objectives. Considerations for choosing the Aikmel Traditional Market where the research was conducted, because the Aikmel Market is classified as the type of vegetables that are sold, it is very complete and the traders there pick them up quite close to the source of the farmers, besides that the Aikmel market provides comfort and peace when transacting. The sampling method is by using the census method.